Phoenix Badminton Academy: Badminton Training Services - Axioma Peano; Anas Hidayat (PT SOLUSI EDUKASI BERDIKARI, 2024)
Phoenix Badminton Academy is a badminton training services business that successfully combines effective business management with innovative operational strategies. This research explores various aspects of the design and implementation of this academy business, starting from market analysis, segmentation, to comprehensive distribution strategies. These findings confirm that investments in training program innovation, facility improvements, and human resource development are critical to ensuring sustainable growth. Phoenix Badminton Academy is committed to providing high-quality services and continuously adapting to industry trends, which makes it a profitable and sustainable business model in the sports industry. The results of this research provide valuable insight for similar business players who want to maximize market potential in the sports training services industry.